Use of Non-Steroid Anti-Inflammatory Drugs (NSAIDs) in Young Women in Neighborhood III Baru Ladang Bambu Village, Medan Tuntungan District, 2018 - Sari Rahma Fitri (Institute of Computer Science (IOCS), 2019)
Menarche or Menstruation is a period of bleeding that occurs in women regularly every month during their fertile period unless pregnancy occurs. Menstruation period is called menses, menstruation, or menstruation. The presence of menstruation is a sign of sexual maturity in adolescent girls. Some women who feel unbearable pain during menstruation can affect 50% of daily activities in women of reproductive age, and 85% in teenage girls. In fact, this condition really needs to be done further by a doctor. This is because this can indicate abnormalities in the reproductive organs, such as uterine infections, cysts or polyps, tumors around the uterus, or it could be due to permanent abnormalities in the position of the uterus.